PENERAPAN METODE PEMBELAJARAN DISCOVERY MENINGKATKAN PRESTASI BELAJAR IPA - Warsiki, Ni Made (Universitas Pendidikan Ganesha, 2018)
This research was conducted in Class IX-8 of Singaraja 2 Public Middle School in the even semester of the 2017/2018 school year, with the aim of improving student learning achievement in science learning by applying discovery methods. Data was collected through a learning achievement tests. Furthermore, the data were analyzed using quantitative descriptive methods. Data was presented in the form of average learning achievement and learning completeness process. The results showed that the learning achievement at the beginning of the average student learning achievement was only 73.63 with learning completeness only 40.74%, then after the implementation of the study it turned out that the student's learning achievement in the first cycle became an average of 79.81. With learning completeness reaching 59.26%, and in the second cycle student learning achievement reached an average of 82.61 with 88.89% learning completeness. Thus the conclusion of this study is that the application of the discovery method can improve student learning achievement in class IX-8 Singaraja SMP Negeri 2 semester even academic year 2017/2018 Keywords: discovery learning method, learning achievement